Effects of online learning on digital literacy during the covid-19 pandemic - Astuti Muh Amin; Fitriyah Karmila; Romi Adiansyah; Noor Hujjatusnaini; Ahmad Yani; Lilin Ika Nur Indahsari (Universitas Ahmad Dahlan, 2022)
Misconceptions are important to know so that future learning can be Digital literacy is one of the skills needed in preparing students to face the challenges of the 21st century. During the Covid-19 pandemic, digital activities have expanded and are increasing because many people have to turn to online alternatives, including teaching and learning activities in schools. The purpose of this study is to identify the effects of online learning on digital literacy during the Covid-19 pandemic. This research is quantitative. The study population was all students at the Senior High School of Ternate City, North Maluku, Indonesia. The research sample was 56 students at State Senior High School 4 of Ternate and State Senior High School 6 of Ternate, North Maluku, Indonesia. The research instruments used in this study were digital literacy instruments, questionnaires on student responses to online learning, questionnaires on learning motivation, and student activity observation sheets. All previous research instruments have been validated by experts and empirically validated. All research instruments have been declared valid and reliable. The results showed that the average score of digital literacy was in the medium category. The hypertext direction guide dimension has the lowest mean score compared to the three dimensions of digital literacy measurement. Digital literacy skills still need to be improved through the empowerment of active and innovative learning models integrated with IT.